Womens Ready-To-Wear Collection: The Reminiscence Of Cambodian Monarch Queen Soma - Loy, Chanreaksmey; Andhini, Grasheli Kusuma (Graduate School of Institut Seni Indonesia Yogyakarta, 2025)
This study aims to reconnect Cambodia with its rich cultural heritage amid cultural similarities that have been happening in Southeast Asia’s neighboring countries. This research used an exploratory descriptive research method with non-probability sampling technique and the application of pattern exploration. Drawing inspiration from a powerful historical figure Queen Soma, the Naga princess, a ready-to-wear collection was created with the fusion of traditional Cambodian attire and contemporary designs. Overall, this study brought a modern approach to traditional clothing to redirect the attention of people towards embracing Cambodian authenticity and promoting its significance to the modern world that could contribute to the cultural preservation. Koleksi Wanita Siap Pakai: Kenangan Raja Pertama Kamboja Ratu Soma Abstrak Penelitian ini bertujuan untuk menghubungkan kembali Kamboja dengan warisan budayanya yang kaya di tengah kesamaan budaya yang terjadi di negara-negara tetangga di Asia Tenggara. Penelitian ini menggunakan metode penelitian deskriptif eksploratif dengan teknik non-probability sampling dan penerapan eksplorasi pola. Mengambil inspirasi dari tokoh sejarah yang kuat, Ratu Soma, putri Naga, koleksi pakaian siap pakai diciptakan dengan perpaduan pakaian tradisional Kamboja dan desain kontemporer. Secara keseluruhan, penelitian ini membawa pendekatan modern terhadap pakaian tradisional untuk mengarahkan kembali perhatian masyarakat terhadap keaslian Kamboja dan mempromosikan signifikansinya bagi dunia modern yang dapat berkontribusi pada pelestarian budaya.